The neuroprotective effect of recombinant human erythropoietin via an antiapoptotic mechanism on hypoxic-ischemic brain injury in neonatal rats - Moon Sun Kim; Yoo Kyung Seo; Hye Jin Park; Kye Hyang Lee; Kyung Hoon Lee; Eun Jin Choi; Jin Kyung Kim; Hai Lee Chung; Woo Taek Kim (Korean Pediatric Society, 2010)
PurposeThe neuroprotective effects of erythropoietin (EPO) have been recently shown in many animal models of brain injury, including hypoxic-ischemic (HI) encephalopathy, trauma, and excitotoxicity; however, limited data are available for such effects during the neonatal periods. Therefore, we investigated whether recombinant human EPO (rHuEPO) can protect against perinatal HI brain injury via an antiapoptotic mechanism.MethodsThe left carotid artery was ligated in 7-day-old Sprague-Dawley (SD) rat pups (in vivo model). The animals were divided into 6 groups: normoxia control (NC), normoxia sham-operated (NS), hypoxia only (H), hypoxia+vehicle (HV), hypoxia+rHuEPO before a hypoxic insult (HE-B), and hypoxia+rHuEPO after a hypoxic insult (HE-A). Embryonic cortical neuronal cell culture of SD rats at 18 days gestation (in vitro model) was performed. The cultured cells were divided into 5 groups: normoxia (N), hypoxia (H), and 1, 10, and 100 IU/mL rHuEPO-treated groups.ResultsIn the in vivo model, Bcl-2 expressions in the H and HV groups were lower than those in the NC and NS groups, whereas those in the HE-A and HE-B groups were greater than those of the H and HV groups. The expressions of Bax and caspase-3 and the ratio of Bax/Bcl-2 were in contrast to those of Bcl-2. In the in vitro model, the patterns of Bcl-2, Bax, and caspase-3 expression and Bax/Bcl-2 ratio were similar to the results obtained in the in vivo model.ConclusionrHuEPO exerts neuroprotective effect against perinatal HI brain injury via an antiapoptotic mechanism.